In situ immune response in human chromoblastomycosis--a possible role for regulatory and Th17 T cells. - Aline Alves de Lima Silva; Paulo Ricardo Criado; Ricardo Spina Nunes; Wellington Luiz Ferreira da Silva; Luciane Kanashiro-Galo; Maria Irma Seixas Duarte; Mirian N Sotto; Carla Pagliari (PLoS Neglected Tropical Diseases)
Background Chromoblastomycosis is a chronic fungal infection that affects skin and subcutaneous tissue. Lesions can be classified in tumorous, verrucous, cicatricial and plaque type. The cellular immune response in the severe form of the disease seems to correlate with a Th2 pattern of cytokines. The humoral immune response also seems to play a role. We intended to explore the populations of regulatory T cells and the Th17 pattern. Methodology Twenty-three biopsies of verrucous form were obtained from patients with clinical, culture and histopathological diagnostic of chromoblastomycosis, without treatment. It was performed an immunohistochemistry method to detect Foxp3, CD25, TGF-β, IL-6, IL-17 and IL-23. Principal findings IL-17 was the only cytokine with high expression in CBM when compared to normal skin. The expression of Treg cells, TGF- β, IL-6 and IL-23 were similar to normal skin. Conclusions/significance The constitution of a local immune response with high expression of IL-17 and low expression of other cytokines could be at least in part, an attempt to help the immune system against fungal infection. On the other hand, high levels of local immune response mediated by Th17 profile could overcome the role of Treg cells. The inefficient immunomodulation as a consequence of the unbalance by Treg/Th17 cells seems to corroborate with the less effective immune response against fungi.